School Health, Nutrition and HIV/AIDS Programming : Promising Practice in the Greater Mekong Sub-Region - Bundy, Donald; O'Connell, Tara; Drake, Lesley; Baker, Simon; Abrioux, Emmanuelle (World Bank, Washington, DC, 2013)
In low income countries, poor health and malnutrition are critical underlying factors for low school enrolment, absenteeism, poor classroom performance and dropout; all of which act as important constraints in countries efforts to achieve Education for All (EFA) and the education Millennium Development Goals (MDGs). In the Greater Mekong Sub-Region (GMSR), the education and health sectors have long recognized that school health and nutrition programs can address the basic health problems faced by their schoolchildren. More recently, life skills modules and HIV prevention education are being introduced to promote positive and healthy behaviors. The currently low levels of HIV infection in the GMSR make a focus on prevention all the more timely. The aim of this document is to share emerging promising practice in the field of school health and nutrition within the GMSR and to inform governments, development partners and other organizations that recognize the need to harmonize activities and align assistance. It aims to strengthen the network of school health, nutrition and HIV/AIDS Ministry of Education Focal Points and further the establishment of a sound community of good practice in the sub-region. The document includes descriptions a wide range of different activities from the six GMSR countries of Cambodia, China (Yunnan Province), Lao People's Democratic Republic (PDR), Myanmar, Thailand and Vietnam.